Hepatitis B e antigen‐suppressing mutations enhance the replication efficiency of adefovir‐resistant hepatitis B virus strains. Issue 2 (3rd July 2012) - Herbers, U.; Amini‐Bavil‐Olyaee, S.; Mueller, A.; Luedde, T.; Trautwein, C.; Tacke, F.
Abstract : Summary.  Hepatitis B e antigen (HBeAg) negative hepatitis B virus (HBV) infections caused by precore (PC) or basal core promoter (BCP) mutations are associated with disease progression and complications. PC or BCP mutations may enhance the replication capacity of distinct drug‐resistance‐associated polymerase mutations, but their effect on adefovir‐resistant HBV mutants is unclear. Importantly, BCP mutations were an independent risk factor for virological breakthrough in lamivudine‐resistant patients treated with adefovir. We aimed at addressing the functional consequences of PC and BCP mutations on the replication and drug susceptibility of adefovir‐resistant HBV mutants. Therefore, HBV constructs with wild type (WT) or adefovir‐resistant rtN236T, rtA181V and rtA181T mutations, with or without concomitant PC or BCP mutations, were analysed in vitro using molecular assays. The adefovir‐resistant polymerase mutations rtN236T, rtA181V and rtA181T showed a drastically reduced viral replication compared with WT. Interestingly, additional PC or BCP mutations enhanced the reduced replication efficacy of adefovir‐resistant constructs and restored HBV replication to WT level. HBV rtA181T mutants displayed abolished hepatitis B surface antigen (HBsAg) secretion, owing to a sW172* stop codon in the overlapping envelope gene. All rtN236T‐ or rtA181V/T‐containing constructs, regardless of concomitant PC or BCP mutations, were resistant to adefovir, but remained susceptible to telbivudine, entecavir and tenofovir. In conclusion, adefovir drug resistance mutations reduced viral replication, which can be significantly increased by additional HBeAg‐suppressing PC or BCP mutations. Because increased HBV replication in HBeAg‐negative patients has been associated with an unfavourable clinical course, close monitoring appears indispensable during adefovir treatment in HBeAg‐negative patients.